Development of a 4-DOF Robotic Arm: Prototype Design - Farhan Mustaffa, Muhammad; Liza Ahmad Shauri, Ruhizan; Izzat Roslan, Muhammad; Asyraf Idris, Muhammad (International Journal of Engineering and Technology, 2018)
This paper discusses the development of a prototype industrial robotic arm. This work is related to the previous project where a seven-degree-of-freedom (DOFs) three fingered robotic hand has been developed for grasping work. However, the working range for the task was just limited to within working range of the robot hand, thus a robot arm is required. The objective of this work was to determine the design of the robot armâ€™s link and joint, components and actuators. The 4-DOF robot arm has four joints to imitate a human upper arm namely joint 1, 2, 3 and 4 that rotate around x, y, and z axes, respectively. The joints move four arm links to get the required posture of the wrist that will be assembled with the hand in future application. The investigation of the components and mechanism was implemented to make sure that they matched in terms of the dimensions and capability to lift the load. DC geared motor with the calculated torque has been selected as the actuators of the four joints. Spur gear was chosen to increase the motor torque by 4:1 ratio due to the unavailability of higher torque low cost motors to lift 2.635 kg of the required payload. 3D mechanical design and simulation using SolidWorks software application were repeated several times to confirm the link-joint motion before the final design proceeds to the fabrication step. Fabricated arm was tested for movement using the control system from a separate study to observe the feasibility of the design. It can be observed that the joints and links were able to move according to their desired positions except joint 1 that is due to the heavy steel material of the spur gears that has caused misalignment of the gears during rotation. Replacing these gears with nylon or ABS material is expected to solve the problem in the next study. Overall, the constructed robot arm proved that the proposed design is able to achieve the design requirements and practically moved in several postures in real time. With minor modification, it will be a good reference for the development of the actual sized arm for the existing hand in the next study. Â